(untitled) (Global Journal of Human-Social Science, 2015)
Balochistan Rural Support Programme (BRSP) is a non-governmental organization working in rural areas of Balochistan province since 1983. Its head office is situated in Quetta, Baluchistan, Pakistan, sub-office is located in Islamabad, and a number of district offices are located in various districts of Balochistan. It is clear that majority of the respondents 90 percent of the sample were male and 10 percent were females in district Mastung Balochistan. The respondents 86.66 percent had availed the loan facility only for once and that too for the first time. 11.66 percent had availed this facility twice and only 11.66 percent of them took loan three times. The respondents 40.00% were 25000, 16.66% were 40000.00, 20.00% were 50000.00, 13.33% were 60000.00 and 10.00% were above 80000.00 rupees amount loans. 30.00% were get for seed, 23.33% were Pesticide, 26.66% were Fertilizer and 16.66% were Others purposes.